Through the nu, we Re.Nu. refocusing and redefining the model of healing environments, in character with Salutogenisis, as a means of attaining optimized conditions of health - De Canha, Nicola Danielle (My University, 2022)
Contemporary healthcare architecture has been seen to resign itself to an archetypal model of healing defined throughout architectural history. Characteristic to this model is the embodiment of dehumanized and non-experiential qualities in its depressive and monolithic nature, subsequently manifesting itself as an a-sensory, a-contextual and indifferent spatial construct. Explicit to the orthodox model of healthcare architecture is its physical manifestation, however its experiential character and rigid programmatic constraints that ‘satisfy’ the process of healing, in terms of the pathogen, are in contestation, which can be understood through the facility which offers an exploration into alternative forms of healing. The healing facility, Re.Nu., confronts and contests this orthodox typology of healthcare architecture predominantly through a process of dematerialization. This process is rooted in the intention to transcend the pathogenic model, to which orthodox healthcare architecture ascribes, as it is detached from human experience, relatability and sensitivity. Thus, the intention of the alternative healing facility is to nurture and restore human health and to rejuvenate the individual through an archite[c]t[ure] that is intrinsically human-centred in its non-orthodox and salutogenic realization. The approach considers alternative forms of healing, which are rooted in nutrition and serve to engage a more holistic process of healing. Throughout the process of design, the focus and honing in on an anthropocentric model enables the redefinition and reconfiguration of quintessential perceptions and characters attributed to healthcare spaces in the contemporary locale as mentioned afore. Thus, healthcare architecture is re-moulded into a humanistic, healing architecture. In conjunction with ‘healing the human,’ the architecture is to extend this practice of healing to its environment, calling for a consciousness towards and a relationship with Biophila within the design responses and processes. The confluence of the thinking of Humanism and Biophilia proposes the potential birth of a hybrid model, ‘Bio Humanism.’
A research report submitted in partial fulfilment of the requirement for the degree of Master of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2022